Changes in Global Tourist Behavior During the Covid-19 Pandemic - Fauzun Fazil; Muhammad Maula Affan; Meiana Maulida Hikmawati; Lenny Kurnia Octaviani (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Purpose: The Covid-19 pandemic has been a challenge for the world community since its inception in December 2019. The rapid and massive transmission to all corners of the world has forced various parties to implement policies that harm many sectors. This includes the tourism industry sector. The industry is required to adapt to new habits by participating in presenting policies that are able to provide safe and comfortable tourism for tourists. However, after the many pressures and prohibitions faced during the Covid-19 pandemic, it indirectly changed people's behavior as tourists. Therefore, this study aims to find out which direction changes in tourist behavior globally during the Covid-19 pandemic.Results and discussions: The results of this study indicate that there is a change in tourist behavior related to destination preferences, transportation, and accommodation.Conclusion: Tourists prefer accommodation in the form of villas and longer duration. Meanwhile, the main priority of tourists during the pandemic is cleanliness and health, so if you want to recover quickly, the tourism industry players from upstream to downstream must be able to present clean and healthy tourism